Normal values for hand grip strength in healthy nigerian adults (2013)
Background: Assessment of hand grip strength is used in a wide range of clinical settings particularly during management of hand injuries and diseases affecting hand function. This study aimed to determine age and gender specific normal values of hand grip strength in healthy adults in Nigeria and compare values obtained with those in the Western population. Materials and methods: Hand grip strength was measured using the Baseline Hydraulic Dynamometer. Results were analyzed with SPSS version 15. Results: Two hundred and forty two participants comprising 163 males and 79 females were recruited. Mean values for hand grip strength on the right and left hands were 32.1 ±7.6kg and 30.7±7.7kg in males and 20.3±5.3kg and 18.7±5.3kg in females. Males showed significantly higher grip strength on the right and left hands (p=0.000, p=0.000) than in females. Grip strength peaked in the 30-39 year age group in males and females. In females a positive correlation was found between the grip strengths in both hands with weight, height and body mass index. Normal grip strength in the Western population is at least 1.6 times higher than in this study. Conclusion: The study has been able to establish normal values for handgrip strength among healthy adults in Nigeria, which differ from that in the Western population. There is the need for further studies in other regions of Nigeria in order to establish national values.